Rapid morphological changes, admixture and invasive success in populations of Ring-necked parakeets (Psittacula krameri) established in Europe - Le Gros, Ariane; Samadi, Sarah; Zuccon, Dario; Cornette, Raphaël; Braun, Michael P.; Senar, Juan Carlos; Clergeau, Philippe (Biological invasions, 2016)
The Ring-necked parakeet (Psittacula krameri), native of Asia and Africa, is a very successful invasive species in Europe: it has been present there for over 50 years. A recent study showed that European invasive populations occupy a colder climatic niche than in their native range but the establishment of this tropical species in temperate regions remains unexplained. Two main hypotheses may explain the success of Ring-necked parakeet in Europe: admixture between individuals from different origins and/or rapid adaptation to new environmental conditions. In this study, we investigated with molecular data the origin of European populations of Ring-necked parakeets to assess whether these populations result from admixture between individuals from different source populations. We also investigated the morphology of individuals from European populations and from the native range to assess whether the invasive populations have morphologically diverged from their source and could have become adapted to European conditions. We found evidence of admixture in some of the European populations but not all of them. Admixture between individuals from different origins within European populations thus cannot explain alone their invasive success. Conversely, we found that the morphology of the individuals from European populations has diverged from the morphology of native individuals, in a similar direction. Rapid adaptation to European environmental conditions via phenotypic plasticity or natural selection could thus be a factor explaining the invasive success of Ring-necked parakeets in Europe.
Gesehen am 16.06.2020